Resin composition, molded product, film, optical film and protective film

JP2025026369APending Publication Date: 2025-02-21MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024125184
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-07-31
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0032】 本発明によれば、特定のポリカーボネート樹脂とシクロオレフィン樹脂とを所定の質量比で含む樹脂組成物であって、透明性、耐熱性、低吸湿性及び加工性に優れた高品質な樹脂組成物を提供することが出来る。また、本発明の樹脂組成物は高いバイオマス度を有しており、持続可能な社会の実現に貢献することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026369000001
    Figure 2025026369000001
  • Figure 2025026369000002
    Figure 2025026369000002
  • Figure 2025026369000003
    Figure 2025026369000003
Patent Text Reader

Abstract

To provide a resin composition that excels in transparency, heat resistance, low hygroscopicity and processability.SOLUTION: The present invention provides a resin composition that comprises two or more resins comprising a heterocyclic backbone and / or an alicyclic backbone as a repeating unit, wherein at least one of the resins is a resin with a carbonate bond, and at least one of the resins is a cycloolefin resin, wherein the content of the cycloolefin resin relative to the total mass of the resin components is less than 86 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a molded article, a film, and an optical film and a protective film using the film. [Background technology]

[0002] Generally, polycarbonate resins are produced using raw materials derived from petroleum resources, but there is concern about the depletion of petroleum resources, and polycarbonates using raw materials derived from biological substances such as plants are in demand. Conventionally, as a method for obtaining polycarbonate resins, a method has been proposed in which isosorbide (hereinafter sometimes abbreviated as ISB), a dihydroxy compound obtained from biomass resources, is used as a monomer component, and a polycarbonate resin is obtained by transesterification with a carbonate diester while distilling off the by-product monohydroxy compound under reduced pressure (see, for example, Patent Document 1). In addition to being used as a molding material taking advantage of its heat resistance, polycarbonate resins obtained from ISB are also being considered for use in optical films mounted on displays and the like, taking advantage of their excellent optical properties (see, for example, Patent Documents 2 to 4).

[0003] Moreover, cycloolefin resins have excellent optical properties, low moisture absorption and high heat resistance, and therefore are used in optical films, mainly optical compensation films (see, for example, Patent Documents 5 to 6). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-24919 A [Patent Document 2] International Publication No. 2016 / 171194 [Patent Document 3] JP 2009-215435 A [Patent Document 4] International Publication No. 2020 / 196482 [Patent Document 5] JP 2017-40727 A [Patent Document 6] JP 2008-274136 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, as disclosed in Patent Documents 1 to 3, ISB-containing polycarbonate resins contain many oxygen atoms and have higher polarity than polycarbonate resins obtained from diols that do not have an ether moiety, such as polycarbonate resins made from aromatic bisphenols. Therefore, ISB-containing polycarbonate resins have higher water absorption than polycarbonate resins made from aromatic bisphenols, and have the disadvantage that the dimensional stability of molded products and films is reduced due to water absorption, and heat resistance is likely to be reduced under humid heat conditions. In addition, Patent Document 4 describes a film using an ISB-containing polycarbonate resin, but there is room for improvement in heat resistance.

[0006] Patent Document 5 describes an optical film containing a cycloolefin resin and a polymer having a fluorene skeleton, but it has been found that the film often has poor affinity with additives, and there is a risk of the additives bleeding out. Furthermore, the material in Patent Document 6 has poor processability for forming different shapes due to its brittleness, and it is very difficult to modify the material.

[0007] The present invention is intended to solve the above problems, and an object of the present invention is to provide a resin composition which does not cause these problems.

[0008] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, discovered that a resin composition containing a resin having a carbonate bond containing a specific structural unit and a cycloolefin resin in a specific mass ratio has excellent transparency, heat resistance, low moisture absorption and processability, and arrived at the present invention described below.

[0009] The above-mentioned problems of the present invention can be solved by the following means.

[0010] [1] A resin composition containing two or more resins each containing a heterocyclic skeleton and / or an alicyclic skeleton as a repeating unit, At least one of the resins has a carbonate bond, At least one of the resins is a cycloolefin resin, A resin composition, in which the content of the cycloolefin resin relative to the total mass of the resin components is less than 86 mass%.

[0011] [2] The resin composition according to [1], wherein the resin having a carbonate bond is a polycarbonate resin containing a structural unit (a) derived from a dihydroxy compound having a moiety represented by the following formula (1):

[0012] [ka]

[0013] [3] The resin composition according to [2], wherein a mass ratio of the polycarbonate resin to the cycloolefin resin is 99:1 to 15:85.

[0014] [4] The resin composition according to [2] or [3], wherein the structural unit (a) is a structural unit represented by the following formula (2) and / or the following formula (3):

[0015] [ka]

[0016] [ka]

[0017] [5] The resin composition according to any one of [2] to [4], wherein the polycarbonate resin contains a structural unit (b) derived from an alicyclic dihydroxy compound.

[0018] [6] The resin composition according to [5], wherein the structural unit (b) is a structural unit represented by the following formula (4):

[0019] [ka]

[0020] [7] The resin composition according to any one of [1] to [6], containing an ultraviolet absorber in an amount of 0.01 to 3.0 mass % based on the total mass of the resin composition.

[0021] [8] The resin composition according to any one of [1] to [7], which has two or more glass transition temperatures.

[0022] [9] The resin composition according to any one of [1] to [8], having at least one glass transition temperature of 130° C. or higher and a saturated water absorption of 1.6 wt % or lower.

[0023]

[10] The resin composition according to any one of [2] to [9], wherein the absolute value of the refractive index difference between the polycarbonate resin and the cycloolefin resin at 589 nm is 0.02 or less.

[0024]

[11] The resin composition according to any one of [1] to

[10] , having a reduced viscosity at 20°C of 0.20 dL / g or more and 0.60 dL / g or less.

[0025]

[12] A molded article obtained by molding the resin composition according to any one of [1] to

[11] .

[0026]

[13] A film comprising the molded article described in

[12] .

[0027]

[14] An optical film comprising the film according to

[13] .

[0028]

[15] A protective film comprising the film described in

[13] .

[0029]

[16] The molded article according to

[12] , having a haze of 20% or less.

[0030]

[17] The molded article according to

[12] , having a total light transmittance of 85% or more.

[0031]

[18] The molded article according to

[12] , having a light transmittance of 60% or less at a wavelength of 380 nm. Effect of the Invention

[0032] According to the present invention, a resin composition containing a specific polycarbonate resin and a cycloolefin resin in a predetermined mass ratio can be provided, which is a high-quality resin composition excellent in transparency, heat resistance, low moisture absorption, and processability. In addition, the resin composition of the present invention has a high biomass content and can contribute to the realization of a sustainable society. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified in any manner without departing from the gist of the present invention. In this specification, when "~" is used with a numerical value or a physical property value before and after it, the values ​​before and after it are included. Furthermore, numerical values ​​or physical values ​​described as upper and lower limits, other than those described as "greater than" or "less than", are used to mean that the value is included. Furthermore, "%" means "% by mass" unless otherwise specified. Furthermore, "parts by weight" and "parts by mass", "% by weight" and "% by mass" are substantially synonymous.

[0034] In the present disclosure, the term "polycarbonate resin" is a concept including not only polycarbonate resin but also polyester carbonate resin. The polyester carbonate resin refers to a polymer in which the structural units constituting the polymer include a portion linked by not only carbonate bonds but also ester bonds.

[0035] The term "structural unit" refers to a partial structure constituting a resin, and a specific partial structure contained in a repeating structural unit. For example, in the case of a polycarbonate resin, it refers to a partial structure sandwiched between adjacent linking groups in the resin, or a partial structure sandwiched between a polymerization reactive group present at the end of a polymer and a linking group adjacent to the polymerization reactive group. More specifically, in the case of a polycarbonate resin, a carbonyl group is a linking group, and a partial structure sandwiched between adjacent carbonyl groups is called a structural unit. In this specification, the mass ratio of each structural unit in the resin is calculated assuming that the total mass of all structural units and linking groups is 100 mass %.

[0036] The following describes in detail an embodiment of the present invention. The description of the components described below is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to the following content as long as it does not exceed the gist of the present invention.

[0037] The resin composition of the present invention contains two or more resins having a heterocyclic skeleton and / or an alicyclic skeleton as a repeating unit, at least one of which is a resin having a carbonate bond, and at least one of which is a cycloolefin resin, and the content of the cycloolefin resin relative to the total mass of the resin components is less than 86 mass%.

[0038] The resin having a carbonate bond in the present invention may have other bonds. Examples of other bonds include ester bonds, urethane bonds, urea bonds, amide bonds, and imide bonds. Among them, from the viewpoints of heat resistance, melt processability, and mechanical strength, it is preferable that the resin has an ester bond in addition to the carbonate bond.

[0039] In the present invention, the resin having a carbonate bond is preferably a polycarbonate resin from the viewpoints of heat resistance, melt processability, and mechanical strength.

[0040] <Polycarbonate resin> The resin having a carbonate bond constituting the resin composition of the present invention is preferably a polycarbonate resin containing a structural unit (a) derived from a dihydroxy compound having a moiety represented by the following formula (1). Hereinafter, this polycarbonate resin may be referred to as the "polycarbonate resin in the present invention."

[0041] [ka]

[0042] The dihydroxy compound having the moiety represented by the formula (1) includes isosorbide (ISB), isomannide, and isoidet, which are stereoisomers. These may be used alone or in combination of two or more. Among them, isosorbide obtained by dehydration condensation of sorbitol produced from various starches, which are abundant and easily available as a plant-derived resource, is most preferable in terms of availability, ease of production, and properties of the molded product obtained (for example, heat resistance, impact resistance, surface hardness). In addition, it is preferable to use isosorbide from the viewpoint of carbon neutrality.

[0043] (Structural unit (a)) The structural unit (a) is preferably a structural unit represented by the following formula (2).

[0044] [ka]

[0045] The mass ratio of the structural unit (a) in the polycarbonate resin in the present invention is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, based on 100% by mass of all structural units constituting the polycarbonate resin. If it is equal to or more than the lower limit, the solidification temperature of the obtained polycarbonate resin can be set to room temperature or higher, and when the polycarbonate resin is made into pellets and handled, the fusion of the pellets can be prevented. In addition, the mass ratio of the structural unit (A) is preferably less than 90% by mass, more preferably 80% by mass or less, and even more preferably 70% by mass or less. If it is equal to or less than the upper limit, the water absorption rate of the polycarbonate resin can be suppressed.

[0046] In addition, examples of dihydroxy compounds having a moiety represented by formula (1) that can be used include spiroglycol (also known as 3,9-bis(1,1-dimethyl-2-hydroxyethyl-2,4,8,10-tetraoxaspiro[5,5]undecane) and dioxane glycol (also known as 2-(1,1-dimethyl-2-hydroxyethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane). Among these, spiroglycol is more preferred. In addition, the structural unit (a) derived from a dihydroxy compound having a moiety represented by formula (1) is preferably a structural unit represented by formula (3) below.

[0047] [ka]

[0048] (Structural unit (b)) The polycarbonate resin in the present invention preferably contains a structural unit (b) in addition to the structural unit (a) from the viewpoint of a balance between optical properties, heat resistance, mechanical properties, etc. Examples of dihydroxy compounds forming the structural unit (b) include aliphatic dihydroxy compounds, alicyclic dihydroxy compounds, ether-containing dihydroxy compounds, aromatic-containing dihydroxy compounds, and diester compounds. Among them, from the viewpoint of weather resistance and moist heat resistance, alicyclic dihydroxy compounds are preferred.

[0049] Examples of the aliphatic dihydroxy compound include the following dihydroxy compounds: linear aliphatic dihydroxy compounds such as ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,5-heptanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol; and branched aliphatic dihydroxy compounds such as 1,3-butanediol, 1,2-butanediol, neopentyl glycol, and hexylene glycol. Among these, 1,6-hexanediol, 1,9-nonanediol, and 1,10-decanediol are preferred.

[0050] Examples of the alicyclic dihydroxy compound include the following dihydroxy compounds: dihydroxy compounds which are primary alcohols of alicyclic hydrocarbons, such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecane dimethanol, 2,6-decalin dimethanol, 1,5-decalin dimethanol, 2,3-decalin dimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol, 1,3-adamantanedimethanol, and dihydroxy compounds derived from terpene compounds such as limonene; dihydroxy compounds which are secondary or tertiary alcohols of alicyclic hydrocarbons, such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,3-adamantanediol, hydrogenated bisphenol A, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol. Among them, tricyclodecane dimethanol and 1,4-cyclohexane dimethanol are more preferable. Furthermore, the structural unit (b) derived from an alicyclic dihydroxy compound is preferably a structural unit represented by the following formula (4).

[0051] [ka]

[0052] Examples of the ether-containing dihydroxy compound include oxyalkylene glycols and dihydroxy compounds containing an acetal ring. Examples of the oxyalkylene glycol that can be used include diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0053] As the aromatic dihydroxy compound, for example, the following dihydroxy compounds can be used: 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3-phenyl)phenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, bis(4-hydroxyphenyl)propane, )methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, 1,1-bis(4-hydroxyphenyl)-2-ethylhexane, 1,1-bis(4-hydroxyphenyl)decane, bis(4-hydroxy-3-nitrophenyl)methane, 3,3-bis(4-hydroxyphenyl)pentane, 1,3-bis(4-hydroxyphenyl)pentane, Bis(2-(4-hydroxyphenyl)-2-propyl)benzene, 1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenyl sulfone, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxy-3-methylphenyl)sulfide, bis(4-hydroxyphenyl)disulfide, 4, Aromatic bisphenol compounds such as 4'-dihydroxydiphenyl ether and 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether; dihydroxy compounds having an ether group bonded to an aromatic group such as 2,2-bis(4-(2-hydroxyethoxy)phenyl)propane, 2,2-bis(4-(2-hydroxypropoxy)phenyl)propane, 1,3-bis(2-hydroxyethoxy)benzene, 4,4'-bis(2-hydroxyethoxy)biphenyl, and bis(4-(2-hydroxyethoxy)phenyl)sulfone;9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxypropoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxypropoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxypropoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene , 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene, 9,9-bis(4-(3-hydroxy-2,2-dimethylpropoxy)phenyl)fluorene and other dihydroxy compounds having a fluorene ring;

[0054] Examples of diester compounds include the following dicarboxylic acids: aromatic dicarboxylic acids such as terephthalic acid, phthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-benzophenonedicarboxylic acid, 4,4'-diphenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, and 2,6-naphthalenedicarboxylic acid; alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. These dicarboxylic acid components can be used as raw materials for polyester carbonate resins as dicarboxylic acids themselves, but depending on the production method, dicarboxylic acid esters such as methyl esters and phenyl esters, and dicarboxylic acid derivatives such as dicarboxylic acid halides can also be used as raw materials.

[0055] The mass ratio of the structural unit (b) in the polycarbonate resin in the present invention is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on 100% by mass of all structural units constituting the polycarbonate resin. If it is equal to or more than the lower limit, the impact resistance of the resulting polycarbonate resin can be improved. In addition, the mass ratio of the structural unit (b) is preferably less than 90% by mass, more preferably 80% by mass or less, and even more preferably 70% by mass or less. If it is equal to or less than the upper limit, the water absorption rate of the polycarbonate resin can be suppressed.

[0056] (Oligofluorene structural unit (A)) The polycarbonate resin in the present invention may contain an oligofluorene structural unit (A) which is a structural unit composed of a structural unit represented by the following formula (5) and / or a structural unit represented by the following formula (6). Hereinafter, this structural unit may be referred to as "oligofluorene structural unit (A)" or "structural unit (A)".

[0057] [ka]

[0058] [ka]

[0059] In formulas (5) and (6), R 1 ~R 3 R each independently represents a direct bond or a substituted or unsubstituted alkylene group having 1 to 4 carbon atoms. 4 ~R 9 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 10 carbon atoms, a substituted or unsubstituted acyl group having 2 to 10 carbon atoms, a substituted or unsubstituted alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted aryloxy group having 6 to 10 carbon atoms, a substituted or unsubstituted amino group, a substituted or unsubstituted vinyl group having 2 to 10 carbon atoms, a substituted or unsubstituted ethynyl group having 2 to 10 carbon atoms, a sulfur atom having a substituent, a silicon atom having a substituent, a halogen atom, a nitro group, or a cyano group. 4 ~R 9 may be the same or different, R 4 ~R 9 At least two adjacent groups among these may be bonded to each other to form a ring. From the viewpoint that the fluorene rings in the polymer are easily oriented perpendicular to the main chain direction and thus exhibit stronger reverse wavelength dispersion, it is preferable that the polycarbonate resin contains a structural unit represented by formula (6).

[0060] R 1 and R 2As R, for example, the following alkylene groups can be used. Specific examples include linear alkylene groups such as methylene, ethylene, n-propylene, and n-butylene; and branched alkylene groups such as methylmethylene, dimethylmethylene, ethylmethylene, propylmethylene, (1-methylethyl)methylene, 1-methylethylene, 2-methylethylene, 1-ethylethylene, 2-ethylethylene, 1-methylpropylene, 2-methylpropylene, 1,1-dimethylethylene, 2,2-dimethylpropylene, and 3-methylpropylene. 1 and R 2 The positions of the branched chains in R are indicated by numbers given so that the carbon on the fluorene ring side is in the 1st position. From the viewpoint that the fluorene rings in the polymer tend to be oriented perpendicular to the main chain direction and thus exhibit stronger reverse wavelength dispersion, 1 and R 2 is preferably an ethylene group.

[0061] R 1 and R 2 The selection of R may be related to the expression of the reverse dispersion wavelength dependency. A polycarbonate resin exhibits the strongest reverse dispersion wavelength dependency when the fluorene rings are oriented perpendicular to the main chain direction (stretching direction). In order to bring the orientation state of the fluorene rings closer to such a state and to express a strong reverse dispersion wavelength dependency, it is preferable to select R having an alkylene group with a main chain carbon number of 2 to 3. 1 and R 2 is preferably adopted. When the carbon number is 1, unexpectedly, there are cases where the reverse dispersion wavelength dependency is not shown. This is considered to be because, for example, the steric hindrance of the carbonate group and / or ester group, which are the linking groups of the oligofluorene structural unit, fixes the orientation of the fluorene ring in a direction that is not perpendicular to the main chain direction. On the other hand, when the carbon number is too large, the fixation of the orientation of the fluorene ring is weakened, and the reverse dispersion wavelength dependency may become insufficient. Furthermore, the heat resistance of the polycarbonate resin may decrease.

[0062] R 3As R, for example, the following alkylene groups can be used. Specific examples include linear alkylene groups such as methylene, ethylene, n-propylene, and n-butylene; and branched alkylene groups such as methylmethylene, dimethylmethylene, ethylmethylene, propylmethylene, (1-methylethyl)methylene, 1-methylethylene, 2-methylethylene, 1-ethylethylene, 2-ethylethylene, 1-methylpropylene, 2-methylpropylene, 1,1-dimethylethylene, 2,2-dimethylpropylene, and 3-methylpropylene. 3 The alkylene group preferably has 1 to 2 carbon atoms on the main chain, and more preferably has 1 carbon atom. When the number of carbon atoms on the main chain is too large, R 1 and R 2 As in the case of , the fixation of the fluorene ring is weakened, which may lead to a decrease in the wavelength dependency of reverse dispersion, an increase in the photoelastic coefficient, a decrease in heat resistance, etc. On the other hand, the optical properties and heat resistance are better when the number of carbon atoms on the main chain is smaller, but when the 9-positions of two fluorene rings are directly bonded, the thermal stability may be deteriorated.

[0063] R 1 ~R 3 Examples of the substituent in the above group include a halogen atom (specifically, a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom); an alkoxy group having 1 to 10 carbon atoms such as a methoxy group or an ethoxy group; an acyl group having 1 to 10 carbon atoms such as an acetyl group or a benzoyl group; an acylamino group having 1 to 10 carbon atoms such as an acetamido group or a benzoylamido group; a nitro group; a cyano group; and an aryl group having 6 to 10 carbon atoms such as a phenyl group or a naphthyl group. One to three hydrogen atoms in the aryl group may be substituted with the above-mentioned halogen atom, alkoxy group, acyl group, acylamino group, nitro group, cyano group, etc.

[0064] R 4 ~R 9As the substituted or unsubstituted alkyl group in, for example, the following alkyl groups can be used. Specific examples include linear alkyl groups such as methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, and n-decyl; branched alkyl groups such as isopropyl, 2-methylpropyl, 2,2-dimethylpropyl, and 2-ethylhexyl; and cyclic alkyl groups such as cyclopropyl, cyclopentyl, cyclohexyl, and cyclooctyl. The number of carbon atoms in the alkyl group is preferably 4 or less, and more preferably 2 or less. When the number of carbon atoms is within this range, steric hindrance between fluorene rings is unlikely to occur, and desired optical properties derived from the fluorene rings are easily obtained. Substituents of the alkyl group include R 1 ~R 3 Examples of the substituents include those mentioned above for the substituents.

[0065] R 4 ~R 9 As the substituted or unsubstituted aryl group in, for example, the following aryl groups can be used. Specific examples include aryl groups such as phenyl, 1-naphthyl, and 2-naphthyl groups; and heteroaryl groups such as 2-pyridyl, 2-thienyl, and 2-furyl groups. The number of carbon atoms in the aryl group is preferably 8 or less, and more preferably 7 or less. When the number of carbon atoms is within this range, steric hindrance between the fluorene rings is unlikely to occur, and the desired optical properties derived from the fluorene rings can be easily obtained. Substituents for the aryl group include R 1 ~R 3 Examples of the substituents include those mentioned above for the substituents.

[0066] R 4 ~R 9As the substituted or unsubstituted acyl group in the above, for example, the following acyl groups can be used. Specific examples include aliphatic acyl groups such as formyl, acetyl, propionyl, 2-methylpropionyl, 2,2-dimethylpropionyl, and 2-ethylhexanoyl; and aromatic acyl groups such as benzoyl, 1-naphthylcarbonyl, 2-naphthylcarbonyl, and 2-furylcarbonyl. The number of carbon atoms in the acyl group is preferably 4 or less, and more preferably 2 or less. When the number of carbon atoms is within this range, steric hindrance between the fluorene rings is unlikely to occur, and the desired optical properties derived from the fluorene rings are easily obtained. Substituents of the acyl group include R 1 ~R 3 Examples of the substituents include those mentioned above for the substituents.

[0067] R 4 ~R 9 As the substituted or unsubstituted alkoxy group or aryloxy group in, for example, the following can be used. Specific examples include a methoxy group, an ethoxy group, an isopropoxy group, a tert-butoxy group, a trifluoromethoxy group, and a phenoxy group. The number of carbon atoms in the alkoxy group or aryloxy group is preferably 4 or less, and more preferably 2 or less. When the number of carbon atoms is within this range, steric hindrance between the fluorene rings is unlikely to occur, and it is easy to obtain the desired optical properties derived from the fluorene ring. As the substituent of the alkoxy group or aryloxy group, R 1 ~R 3 Examples of the substituents include those mentioned above for the substituents.

[0068] R 4 ~R 9The substituted or unsubstituted amino group in may be, for example, the following amino groups. Specifically, the amino groups include: aliphatic amino groups such as N-methylamino, N,N-dimethylamino, N-ethylamino, N,N-diethylamino, N,N-methylethylamino, N-propylamino, N,N-dipropylamino, N-isopropylamino, and N,N-diisopropylamino; aromatic amino groups such as N-phenylamino and N,N-diphenylamino; acylamino groups such as formamide, acetamide, decanoylamide, benzoylamide, and chloroacetamide; and alkoxycarbonylamino groups such as benzyloxycarbonylamino and tert-butyloxycarbonylamino. The amino group is preferably an N,N-dimethylamino, N-ethylamino, or N,N-diethylamino group, and more preferably an N,N-dimethylamino group. In this case, since the amino group does not have a highly acidic proton and has a small molecular weight, the fluorene ratio can be increased, which not only improves the thermal stability but also reduces the amount of monomers having oligofluorene structural units.

[0069] R 4 ~R 9 The following can be used as the substituted or unsubstituted vinyl or ethynyl group in the above. Specifically, vinyl, 2-methylvinyl, 2,2-dimethylvinyl, 2-phenylvinyl, 2-acetylvinyl, ethynyl, methylethynyl, tert-butylethynyl, phenylethynyl, acetylethynyl, and trimethylsilylethynyl groups can be mentioned. The number of carbon atoms in the vinyl or ethynyl group is preferably 4 or less. When the number of carbon atoms is within this range, steric hindrance between fluorene rings is unlikely to occur, and the desired optical properties derived from the fluorene rings can be easily obtained. In addition, the conjugated system of the fluorene ring is long, making it easier to obtain a stronger reverse dispersion wavelength dependency.

[0070] R 4 ~R 9As the sulfur atom having a substituent in the above, for example, the following sulfur-containing groups can be used. Specific examples of the alkyl group include a sulfo group; alkylsulfonyl groups such as a methylsulfonyl group, an ethylsulfonyl group, a propylsulfonyl group, and an isopropylsulfonyl group; arylsulfonyl groups such as a phenylsulfonyl group and a p-tolylsulfonyl group; alkylsulfinyl groups such as a methylsulfinyl group, an ethylsulfinyl group, a propylsulfinyl group, and an isopropylsulfinyl group; arylsulfinyl groups such as a phenylsulfinyl group and a p-tolylsulfinyl group; alkylthio groups such as a methylthio group and an ethylthio group; arylthio groups such as a phenylthio group and a p-tolylthio group; alkoxysulfonyl groups such as a methoxysulfonyl group and an ethoxysulfonyl group; aryloxysulfonyl groups such as a phenoxysulfonyl group; an aminosulfonyl group; alkylsulfonyl groups such as an N-methylaminosulfonyl group, an N-ethylaminosulfonyl group, an N-tert-butylaminosulfonyl group, an N,N-dimethylaminosulfonyl group, and an N,N-diethylaminosulfonyl group; and arylaminosulfonyl groups such as an N-phenylaminosulfonyl group and an N,N-diphenylaminosulfonyl group. The sulfo group may form a salt with lithium, sodium, potassium, magnesium, ammonium, etc. As the sulfur-containing group, a methylsulfinyl group, an ethylsulfinyl group, or a phenylsulfinyl group is preferred, and a methylsulfinyl group is more preferred. In this case, the sulfur-containing group does not have a proton with high acidity, and the molecular weight of the sulfur-containing group is small, so that the fluorene ratio can be increased. Therefore, in addition to improving the thermal stability, the amount of monomer having an oligofluorene structure unit can be reduced.

[0071] R 4 ~R 9 As the silicon atom having a substituent in the above, for example, the following silyl groups can be used. Specific examples include trialkylsilyl groups such as trimethylsilyl group and triethylsilyl group; and trialkoxysilyl groups such as trimethoxysilyl group and triethoxysilyl group. Trialkylsilyl groups are preferred because they are excellent in stability and ease of handling.

[0072] Also, R 4 ~R 9 In the above, the halogen atom may be, for example, a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom. Among these, it is preferable to adopt a fluorine atom, a chlorine atom, or a bromine atom, and it is more preferable to adopt a chlorine atom or a bromine atom, from the viewpoint that it is relatively easy to introduce and has an electron-withdrawing property and therefore tends to increase the reactivity of the 9-position of fluorene.

[0073] R 4 ~R 9 Specific examples of rings formed by bonding at least two adjacent groups include substituted fluorene structures as shown in the following group [I]. In the following group [I], the wavy line indicates the bond between the 9-position of the fluorene structure and R 1 and R 2 Or R 2 and R 3 This indicates that the bond leading to

[0074] [ka]

[0075] In addition to being able to adjust the wavelength dispersion of the polycarbonate resin to a desired range, from the viewpoint of improving mechanical properties, the content of the structural unit (A) relative to the total amount of all structural units and linking groups constituting the polycarbonate resin (100% by mass) is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more. In addition to reducing the photoelastic coefficient of the polycarbonate resin, it is expected that the expression of retardation is improved, and the ratio of the structural unit (A) in the resin can be reduced, which widens the scope of molecular design and makes it easier to improve when modification of the resin is required. From this viewpoint, the content of the structural unit (A) is preferably 45% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less. Specifically, the linking group is a carbonate group or an ester group present at the end of each structural unit. The content of structural unit (A) is the total content of the structural unit represented by formula (5) and the structural unit represented by formula (6), and when only one of the structural units is contained, the content of the other is 0.

[0076] The method of adjusting the ratio of the oligofluorene structural unit (A) in the polycarbonate resin in the present invention includes, for example, copolymerizing a monomer having the oligofluorene structural unit (A) with another monomer, or blending a resin containing the oligofluorene structural unit (A) with another resin. The method of copolymerizing a monomer having the oligofluorene structural unit (A) with another monomer is preferred because it can precisely control the content of the oligofluorene structural unit (A), can obtain high transparency, and can obtain uniform properties over the entire surface of the film.

[0077] The polycarbonate resin in the present invention may be used alone or in combination of two or more kinds.

[0078] (carbonic acid diester) The linking group of the above structural unit contained in the polycarbonate resin in the present invention is introduced by polymerizing a carbonate diester represented by the following formula (9).

[0079] [ka]

[0080] (In formula (7), R 10 and R 11 each represents an aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, or an aromatic hydrocarbon group which may have a substituent, and R 10 and R 11 may be the same or different.)

[0081] R 10 and R 11 is preferably a substituted or unsubstituted aromatic hydrocarbon group, more preferably an unsubstituted aromatic hydrocarbon group. Examples of the substituent of the aliphatic hydrocarbon group include an ester group, an ether group, an amide group, and a halogen atom, and examples of the substituent of the aromatic hydrocarbon group include an alkyl group such as a methyl group or an ethyl group.

[0082] Examples of the carbonic acid diester represented by the formula (4) include diphenyl carbonate (hereinafter sometimes abbreviated as DPC), substituted diphenyl carbonate such as ditolyl carbonate, and dialkyl carbonate such as dimethyl carbonate, diethyl carbonate, and di-tert-butyl carbonate, with diphenyl carbonate and substituted diphenyl carbonate being preferred, and diphenyl carbonate being particularly preferred.

[0083] The carbonate diester may contain impurities such as chloride ions, and these impurities may inhibit the polymerization reaction or deteriorate the hue of the resulting resin. Therefore, it is preferable to use a diester that has been purified, as necessary, by distillation or the like.

[0084] The polycarbonate resin of the present invention can be synthesized by a process of polycondensation by transesterification using a dihydroxy compound forming at least the structural unit represented by the structural unit (a) and a carbonic acid diester as raw materials. More specifically, the polycarbonate resin can be obtained by removing, from the system, monohydroxy compounds and the like that are by-produced in the transesterification reaction during the polycondensation.

[0085] <Production method of polycarbonate resin> The transesterification reaction proceeds in the presence of a transesterification catalyst (hereinafter, the transesterification catalyst is referred to as a "polymerization catalyst.") The type of polymerization catalyst can have a significant effect on the reaction rate of the transesterification reaction and the quality of the resulting polycarbonate resin.

[0086] The polymerization catalyst is not particularly limited as long as it can satisfy the transparency, color tone, heat resistance, weather resistance, and mechanical properties of the resulting polycarbonate resin. For example, metal compounds of Group I or Group II (hereinafter simply referred to as "Group 1" and "Group 2") in the long-form periodic table, as well as basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds, and amine compounds can be used as the polymerization catalyst. Among them, Group 1 metal compounds and / or Group 2 metal compounds are preferred.

[0087] Examples of Group 1 metal compounds include the following compounds: sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium hydrogen carbonate, potassium hydrogen carbonate, lithium hydrogen carbonate, cesium hydrogen carbonate, sodium carbonate, potassium carbonate, lithium carbonate, cesium carbonate, sodium acetate, potassium acetate, lithium acetate, cesium acetate, sodium stearate, potassium stearate, lithium stearate, cesium stearate, sodium borohydride, potassium borohydride, lithium borohydride, cesium borohydride, sodium phenylborohydride, and boron phenylide. Potassium, lithium phenyl boron, cesium phenyl boron, sodium benzoate, potassium benzoate, lithium benzoate, cesium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, dicesium hydrogen phosphate, disodium phenylphosphate, dipotassium phenylphosphate, dilithium phenylphosphate, dicesium phenylphosphate, alcoholates, phenolates of sodium, potassium, lithium, and cesium, and disodium salts, dipotassium salts, dilithium salts, and dicesium salts of bisphenol A. As the Group 1 metal compound, lithium compounds are preferred from the viewpoints of polymerization activity and the color tone of the resulting polycarbonate resin.

[0088] Examples of Group 2 metal compounds include the following compounds: calcium hydroxide, barium hydroxide, magnesium hydroxide, strontium hydroxide, calcium hydrogen carbonate, barium hydrogen carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium carbonate, barium carbonate, magnesium carbonate, strontium carbonate, calcium acetate, barium acetate, magnesium acetate, strontium acetate, calcium stearate, barium stearate, magnesium stearate, and strontium stearate. As the Group 2 metal compound, magnesium compounds, calcium compounds, or barium compounds are preferred, and from the viewpoints of polymerization activity and color tone of the resulting polycarbonate resin, barium compounds, magnesium compounds, and / or calcium compounds are more preferred, and calcium compounds are most preferred.

[0089] Although it is possible to use a basic compound such as a basic boron compound, a basic phosphorus compound, a basic ammonium compound, or an amine compound in combination with the Group 1 metal compound and / or the Group 2 metal compound, it is more preferable to use only the Group 1 metal compound and / or the Group 2 metal compound, and from the viewpoint of the color tone of the obtained polycarbonate resin, it is most preferable to use only the Group 2 metal compound.

[0090] The amount of the polymerization catalyst used is preferably 1 μmol or more, more preferably 3 μmol or more, and particularly preferably 5 μmol or more per mol of the total dihydroxy compounds used in the reaction, and is preferably 300 μmol or less, more preferably 200 μmol or less, and particularly preferably 100 μmol or less per mol of the total dihydroxy compounds used in the reaction.

[0091] By adjusting the amount of the polymerization catalyst used within the above range, the polymerization rate can be increased, and therefore it is possible to obtain a polycarbonate resin with a desired molecular weight without necessarily increasing the polymerization temperature, and therefore it is possible to suppress deterioration in the color tone of the polycarbonate resin. In addition, it is possible to prevent the unreacted raw materials from volatilizing during the polymerization, which would cause the molar ratio of the dihydroxy compound and the carbonic acid diester to be lost, and therefore it is possible to more reliably obtain a resin with a desired molecular weight and copolymerization ratio. Furthermore, it is possible to suppress the occurrence of side reactions, and therefore it is possible to further prevent deterioration in the color tone of the polycarbonate resin or coloring during molding.

[0092] Considering the adverse effects of sodium, potassium, and cesium among the group 1 metals on the color tone of the polycarbonate resin, and the adverse effects of iron on the color tone of the polycarbonate resin, the total content of sodium, potassium, cesium, and iron in the polycarbonate resin is preferably 1 ppm by weight or less. In this case, the deterioration of the color tone of the polycarbonate resin can be further prevented, and the color tone of the polycarbonate resin can be further improved. From the same viewpoint, the total content of sodium, potassium, cesium, and iron in the polycarbonate resin is more preferably 0.5 ppm by weight or less. Note that these metals may be mixed not only from the catalyst used, but also from the raw materials or reaction equipment. Regardless of the source, the total amount of the compounds of these metals in the polycarbonate resin is preferably within the above-mentioned range as the total content of sodium, potassium, cesium, and iron.

[0093] The method of polycondensing a dihydroxy compound and a carbonic acid diester is carried out in multiple stages using multiple reactors in the presence of the above-mentioned catalyst. The reaction may be carried out in a batchwise manner, a continuous manner, or a combination of a batchwise manner and a continuous manner, but it is preferable to adopt a continuous manner, which is excellent in productivity and can obtain a polycarbonate resin with less heat history.

[0094] The dihydroxy compound and the carbonic acid diester, which are the raw materials, are preferably melted separately or mixed uniformly before the transesterification reaction. The melting or mixing temperature is usually 80° C. or higher, preferably 90° C. or higher, and usually 200° C. or lower, preferably 150° C. or lower, and particularly preferably 120° C. or lower. In this case, the dissolution rate can be increased and the solubility can be sufficiently improved, and problems such as solidification can be sufficiently avoided. Furthermore, in this case, the thermal deterioration of the dihydroxy compound can be sufficiently suppressed, and the quality, represented by the color tone, of the obtained polycarbonate resin can be further improved.

[0095] From the viewpoint of controlling the polymerization rate and the quality of the resulting polycarbonate resin, it is important to appropriately select the jacket temperature, the internal temperature, and the pressure in the reaction system according to the reaction stage. Specifically, it is preferable to obtain a prepolymer at a relatively low temperature and low vacuum in the early stage of the polycondensation reaction, and to increase the molecular weight to a predetermined value at a relatively high temperature and high vacuum in the later stage of the reaction. In this case, the distillation of unreacted monomers is suppressed, and it becomes easier to adjust the molar ratio of the dihydroxy compound and the carbonate diester to a desired ratio. As a result, the decrease in the polymerization rate can be suppressed. In addition, it becomes possible to more reliably obtain a polymer having a desired molecular weight and terminal group.

[0096] By adjusting the temperature of the polycondensation reaction, it is possible to improve productivity and prevent the increase of the heat history of the product. Furthermore, it is possible to further prevent the volatilization of the monomer and the decomposition and coloration of the polycarbonate resin. Specifically, the following conditions can be adopted as the reaction conditions in the first stage reaction. That is, the maximum temperature inside the polymerization reactor is set in the range of usually 160 to 230°C, preferably 170 to 220°C, and more preferably 180 to 210°C. In addition, the pressure of the polymerization reactor (hereinafter, pressure refers to absolute pressure) is set in the range of usually 1 to 110 kPa, preferably 5 to 50 kPa, and more preferably 7 to 30 kPa. In addition, the reaction time is set in the range of usually 0.1 to 10 hours, preferably 1 to 5 hours. It is preferable that the first stage reaction is carried out while distilling off the generated monohydroxy compound outside the reaction system.

[0097] From the second stage onwards, it is preferable to gradually reduce the pressure of the reaction system from the pressure of the first stage, and to finally reduce the pressure (absolute pressure) of the reaction system to 1 kPa or less while removing the monohydroxy compound generated subsequently from the reaction system. The maximum internal temperature of the polymerization reactor in the final stage is set in the range of usually 200 to 265°C, preferably 210 to 250°C, and particularly preferably 215 to 245°C. The reaction time in the final stage is usually 0.1 to 20 hours, preferably 0.5 to 15 hours.

[0098] The polycarbonate resin in the present invention to be kneaded with the cycloolefin resin is preferably used for optical applications, so that the polycarbonate resin preferably contains less foreign matter. In order to remove foreign matter such as scorch and gel from the polycarbonate resin obtained by melt polycondensation, it is preferable to perform filtration using a filter. In particular, it is preferable to remove residual monomers and by-product phenols by devolatilization under reduced pressure, and to mix additives such as heat stabilizers and mold release agents by melt extruding the polycarbonate resin using the vented twin-screw extruder and then filtering it with a filter.

[0099] The filter may be of any known form, such as a candle type, a pleated type, or a leaf disk type. The aperture of the filter is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 20 μm or less, in terms of 99% filtration accuracy. When it is particularly desired to reduce foreign matter, the aperture of the filter is preferably 10 μm or less, but if the aperture is small, the pressure loss in the filter increases, which may lead to damage to the filter or deterioration of the polycarbonate resin due to shear heat, so the aperture of the filter is preferably 1 μm or more in terms of 99% filtration accuracy. The aperture of the filter referred to here is determined in accordance with ISO16889.

[0100] The polycarbonate resin filtered through the filter is discharged from the die head in the form of strands, cooled and solidified, and pelletized using a rotary cutter or the like. However, when stranding or pelletizing the polycarbonate resin, which comes into direct contact with the outside air, it is desirable to carry out this process in a clean room that is preferably Class 7, more preferably Class 6, defined in JIS B 9920-1 (2019), in order to prevent contamination by foreign matter from the outside air.

[0101] In pelletizing, it is preferable to use cooling methods such as air cooling and water cooling, and it is preferable to use air that has been previously removed of foreign matter in the air using a HEPA filter or the like to prevent reattachment of foreign matter in the air. When using water cooling, it is preferable to use water that has been removed of metals in the water using an ion-exchange polycarbonate resin or the like and further removed of foreign matter in the water using a water filter. The mesh size of the water filter used is preferably 10 to 0.45 μm, which is a filtration accuracy of 99% removal.

[0102] The polycarbonate resin in the present invention can be generally cooled and solidified after polymerization as described above, and pelletized with a rotary cutter, etc. The pelletization method is not limited, but examples thereof include a method in which the polycarbonate resin is withdrawn in a molten state from the final polymerization reactor, cooled and solidified in the form of strands, and pelletized, a method in which the polycarbonate resin is supplied in a molten state from the final polymerization reactor to a single-screw or twin-screw extruder, melt-extruded, cooled and solidified, and pelletized, or a method in which the polycarbonate resin is withdrawn in a molten state from the final polymerization reactor, cooled and solidified in the form of strands, pelletized once, and then supplied to a single-screw or twin-screw extruder again, melt-extruded, cooled and solidified, and pelletized.

[0103] (Various additives) The polycarbonate resin in the present invention may be blended with additives such as antioxidants, heat stabilizers, neutralizers, light stabilizers, release agents, colorants, antistatic agents, lubricants, plasticizers, compatibilizers, flame retardants, and fillers, as necessary. The additives may also be mixed using a tumbler, super mixer, floater, V-type blender, Nauta mixer, Banbury mixer, extruder, etc. The blending of additives will be described for polycarbonate resin, but they may be blended during polymerization and production of cycloolefin resin, or may be blended during kneading of polycarbonate resin and cycloolefin resin in the present invention.

[0104] Catalyst deactivator The color tone and thermal stability can be improved by adding an acidic compound to the polycarbonate resin of the present invention in order to neutralize and deactivate the catalyst used in the polymerization reaction. As the acidic compound used as the catalyst deactivator, a compound having a carboxylic acid group, a phosphoric acid group, or a sulfonic acid group, or an ester thereof, can be used, but it is particularly preferable to use a phosphorus-based compound containing a partial structure represented by the following formula (8) or (9).

[0105] [ka]

[0106] [ka]

[0107] Examples of the phosphorus-based compound represented by the formula (8) or (9) include phosphoric acid, phosphonic acids, hypophosphorous acid, polyphosphoric acid, phosphonic acid esters, acidic phosphate esters, etc. Among the above, phosphonic acids and phosphonic acid esters are more effective in deactivating the catalyst and inhibiting coloration, and phosphonic acid (phosphorous acid), which is a phosphonic acid, is particularly preferred.

[0108] Examples of the phosphonic acids include phosphonic acid (phosphorous acid), methylphosphonic acid, ethylphosphonic acid, vinylphosphonic acid, decylphosphonic acid, phenylphosphonic acid, benzylphosphonic acid, aminomethylphosphonic acid, methylene diphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, 4-methoxyphenylphosphonic acid, nitrilotris(methylenephosphonic acid), and propylphosphonic anhydride.

[0109] Examples of the phosphonate ester include dimethyl phosphonate, diethyl phosphonate, bis(2-ethylhexyl) phosphonate, dilauryl phosphonate, dioleyl phosphonate, diphenyl phosphonate, dibenzyl phosphonate, dimethyl methylphosphonate, diphenyl methylphosphonate, diethyl ethylphosphonate, diethyl benzylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, dipropyl phenylphosphonate, diethyl (methoxymethyl)phosphonate, diethyl vinylphosphonate, hydroxymethyl diethyl p-methylbenzylphosphonate, diethylphosphonoacetic acid, ethyl diethylphosphonoacetate, tert-butyl diethylphosphonoacetate, diethyl (4-chlorobenzyl)phosphonate, diethyl cyanophosphonate, diethyl cyanomethylphosphonate, diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, diethylphosphonoacetaldehyde diethyl acetal, and diethyl (methylthiomethyl)phosphonate.

[0110] Examples of the acidic phosphate ester include phosphate diesters such as dimethyl phosphate, diethyl phosphate, divinyl phosphate, dipropyl phosphate, dibutyl phosphate, bis(butoxyethyl) phosphate, bis(2-ethylhexyl) phosphate, diisotridecyl phosphate, dioleyl phosphate, distearyl phosphate, diphenyl phosphate, and dibenzyl phosphate, or mixtures of diesters and monoesters, diethyl chlorophosphate, and zinc stearyl phosphate.

[0111] These may be used alone or in any combination and ratio of two or more.

[0112] If the amount of the phosphorus-based compound added to the polycarbonate resin in the present invention is too small, the effect of catalyst deactivation and coloring inhibition is insufficient, and if the amount is too large, the resin is colored, and the resin is more likely to be colored, especially in a durability test under high temperature and high humidity. The amount of the phosphorus-based compound is added in an amount corresponding to the amount of catalyst used in the polymerization reaction. The amount of the phosphorus-based compound is preferably 0.5 times or more and 5 times or less in terms of the amount of phosphorus atoms relative to 1 mol of the metal catalyst used in the polymerization reaction, more preferably 0.7 times or more and 4 times or less in terms of the amount of phosphorus atoms, and particularly preferably 0.8 times or more and 3 times or less in terms of the amount of phosphorus atoms.

[0113] Heat stabilizer The polycarbonate resin of the present invention may contain a heat stabilizer, if necessary, in order to prevent a decrease in molecular weight or deterioration in color during melt processing, etc. Examples of such heat stabilizers include commonly known hindered phenol-based heat stabilizers and / or phosphorus-based heat stabilizers.

[0114] Examples of the hindered phenol compounds include 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2-tert-butyl-4-methoxyphenol, 2-tert-butyl-4,6-dimethylphenol, 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-ethylphenol, 2,5-di-tert-butylhydroquinone, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methylphenyl)propionate, and the like. 2,2'-methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(6-cyclohexyl-4-methylphenol), 2,2'-ethylidene-bis-(2,4-di-tert-butylphenol), tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]-methane, 1,3,5-trimethyl-2,4,6-tris-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, and the like can be used. Among these, it is preferable to use tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]-methane, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-tris-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

[0115] As the phosphorus-based compound, for example, phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid, and esters thereof shown below can be used, but phosphorus-based compounds other than these compounds can also be used. For example, triphenyl phosphite, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite , bis(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tributyl phosphate, triethyl phosphate, trimethyl phosphate, triphenyl phosphate, diphenyl monoorthoxenyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, 4,4'-biphenylenediphosphinic acid tetrakis(2,4-di-tert-butylphenyl), benzene phosphonic acid dimethyl, benzene phosphonic acid diethyl, benzene phosphonic acid dipropyl, etc. These heat stabilizers may be used alone or in combination of two or more.

[0116] Such a heat stabilizer may be added to the reaction liquid during melt polymerization, or may be added to the resin using an extruder and kneaded. When forming a film by melt extrusion, the heat stabilizer may be added to the extruder to form a film, or the heat stabilizer may be added in advance to the resin using an extruder and formed into pellets or the like.

[0117] The amount of these heat stabilizers is, relative to 100 parts by mass of the polycarbonate resin, preferably 0.0001 parts by mass or more, more preferably 0.0005 parts by mass or more, and even more preferably 0.001 parts by mass or more, and is preferably 1 part by mass or less, more preferably 0.5 parts by mass or less, and even more preferably 0.3 parts by mass or less.

[0118] (Light stabilizer) Examples of light stabilizers include 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), and 2,2'-p-phenylenebis(1,3-benzoxazin-4-one).

[0119] These light stabilizers may be used alone or in combination of two or more. The blending amount of such light stabilizers is preferably 0.01 to 2 parts by mass when the polycarbonate resin is 100 parts by mass. In addition, a bluing agent can be blended in the polycarbonate resin according to the present invention to counteract the yellowish color due to the polymer or ultraviolet absorber. As the bluing agent, any agent that is used for polycarbonate resins can be used without any particular problems. In general, anthraquinone dyes are easily available and are preferable.

[0120] Specific examples of bluing agents include Solvent Violet 13 (CA. No. (Color Index No.) 60725), Solvent Violet 31 (CA. No. 68210), Solvent Violet 33 (CA. No. 60725), Solvent Blue 94 (CA. No. 61500), Solvent Violet 36 (CA. No. 68210), Solvent Blue 97 (Bayer's "Macrolex Violet RR") and Solvent Blue 45 (CA. No. 61110).

[0121] These bluing agents may be used alone or in combination of two or more. These bluing agents are usually used in an amount of 0.1×10 -4 ~2×10 -4 It is mixed in a ratio of parts by mass.

[0122] <Characteristics of polycarbonate resin> (Glass transition temperature (Tg)) The glass transition temperature (Tg) of the polycarbonate resin in the present invention is preferably 80° C. or higher, more preferably 100° C. or higher. When the glass transition temperature is above the lower limit, the risk of the polycarbonate resin adhering and deforming at room temperature is reduced. In addition, the glass transition temperature of the polycarbonate resin is preferably 150° C. or lower, more preferably 145° C. or lower, and even more preferably 140° C. or lower. When the glass transition temperature is below the upper limit, the polycarbonate resin is less likely to become brittle, and when produced by melt polymerization, the melt viscosity is reduced, making it easier to produce.

[0123] (Refractive Index) The refractive index of the polycarbonate resin in the present invention is preferably 1.47 or more, more preferably 1.49 or more, and is preferably 1.56 or less, more preferably 1.54 or less. When the refractive index is within the above range, the refractive index is smaller than that of the cycloolefin resin, and the transparency of the resin composition can be increased.

[0124] <Cycloolefin resin> The type of cycloolefin resin constituting the resin composition of the present invention is not limited. Cycloolefin resins are also available as commercial products, such as "ZEONOR" and "ZEONEX" manufactured by Zeon Corporation, "ARTON" manufactured by JSR Corporation, "TOPAS" manufactured by Polyplastics Co., Ltd., and "APEL" manufactured by Mitsui Chemicals, Inc.

[0125] The cycloolefin unit is a structural unit formed by polymerization of, for example, norbornene and its derivatives. An example of the structural unit is shown in the following formula (10).

[0126] [ka]

[0127] In the above formula (10), R 12 and R 13 are each independently a hydrogen atom or a hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 1 to 12. X and Y are each independently a hydrogen atom, a hydrocarbon group, or the following functional group (A). The number of carbon atoms in the hydrocarbon group is preferably 1 to 12. n is an integer, preferably an integer of 0 to 2, and more preferably 0 or 1. The functional group (A) is a hydroxyl group, a hydrocarbon group having a hydroxyl group bonded thereto, a carboxyl group, a hydrocarbon group having a carboxyl group bonded thereto (including a carboxyl ester group; the same applies below), a primary amino group, a secondary amino group, a hydrocarbon group having these amino groups bonded thereto, a quaternary ammonium salt of these amino groups, an amide group, an N-substituted hydrocarbon group and an amide group having an N-active hydrogen, a hydrocarbon group having these amide groups bonded thereto, and an imide group formed by bonding X and Y and represented by -CO-NH-CO-.

[0128] The carbon atom on the ring structure to which the functional group (A) is bonded as X and / or Y is R 12 and / or R 13 It is preferable that a hydrocarbon group is bonded to X and / or Y instead of a hydrogen atom, and it is preferable that an aliphatic hydrocarbon group having 1 or 2 carbon atoms is bonded to X and / or Y. It is preferable that a hydrogen atom is bonded to the carbon atom on the ring structure to which the hydrogen atom is bonded to X and / or Y. In these cases, the thermal decomposition resistance of the cycloolefin resin is increased, so that the thermal decomposition of the cycloolefin resin during melt molding is suppressed, and for example, the occurrence of optical defects in the finally obtained transparent film is suppressed. A transparent film in which the occurrence of optical defects is suppressed is suitable for use as an optical film such as a retardation film or a protective film.

[0129] The functional group (A) is preferably a carboxyl group, a hydrocarbon group having a carboxyl group bonded thereto, an amide group, or an imide group, and more preferably a hydrocarbon group having a carboxyl group bonded thereto.

[0130] The cycloolefin unit may be a unit formed by copolymerization of a cycloolefin monomer that forms the ring structure shown in the above formula (10) upon polymerization with ethylene, or a unit formed by copolymerization of a cycloolefin monomer that forms the ring structure shown in the above formula (10) upon polymerization with acetylene. The former unit is shown in the following formula (11), and the latter unit is shown in the following formula (12). R in the following formulas (11) and (12) 12 , R 13 , X and Y are R in the above formula (10). 12 , R 13 , X and Y, respectively.

[0131] [ka]

[0132] [ka]

[0133] The cycloolefin resin preferably has a structural unit represented by the following formula (15): The presence of a polar group improves compatibility with the polycarbonate resin of the present invention.

[0134] [ka]

[0135] In the above formula (13), R 14 is a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms, and R 15 R is a hydrocarbon group having 1 to 12 carbon atoms. Examples of the hydrocarbon group include a methyl group, an ethyl group, a propyl group, an i-propyl group, a butyl group, and a t-butyl group. 14 is preferably a hydrogen atom or a methyl group, and R 15 is preferably a methyl group or an ethyl group.

[0136] The cycloolefin resin having the structural unit represented by the above formula (13) has excellent heat resistance and durability, and therefore the heat resistance and durability of the molded article or film made from the resin composition of the present invention are improved.

[0137] (Characteristics of cycloolefin resin) Glass transition temperature (Tg) The glass transition temperature (Tg) of the cycloolefin resin in the present invention is usually 110° C. or higher, preferably in the range of 110 to 350° C., more preferably in the range of 120 to 250° C., and even more preferably in the range of 120 to 200° C. If the glass transition temperature (Tg) is 110° C. or higher, deformation under high temperature conditions is easily suppressed. On the other hand, if the glass transition temperature (Tg) is 350° C. or lower, molding is facilitated and deterioration of the resin due to heat during molding is also easily suppressed.

[0138] Refractive Index The refractive index of the cycloolefin resin in the present invention is preferably 1.47 or more, more preferably 1.49 or more, and is preferably 1.56 or less, more preferably 1.54 or less. Within the above range, the difference in refractive index with a resin containing a heterocyclic skeleton and / or an alicyclic skeleton as a repeating unit is reduced, and the transparency of the resin composition can be increased.

[0139] <Resin composition> The resin composition of the present invention contains less than 86% by mass of cycloolefin resin based on the total mass of the resin components. By being within the above range, brittleness can be improved and processability can be imparted. From the same viewpoint, the content of cycloolefin resin is preferably 75% by mass or less, more preferably 60% by mass or less. In addition, it is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more.

[0140] The resin composition of the present invention preferably contains 14% by mass or more and 99% by mass or less of a resin having a carbonate bond relative to the total mass of the resin components. By being within the above range, flexibility can be imparted and processability is improved. From the same viewpoint, the content of the resin having a carbonate bond is more preferably 25% by mass or more and 95% by mass or less, and further preferably 40% by mass or more and 90% by mass or less.

[0141] The resin composition of the present invention may further contain other resins (hereinafter, sometimes referred to as "other resins"). Examples of other resins include synthetic resins such as aromatic polycarbonate resins, aromatic polyesters, aliphatic polyesters, polyamides, polystyrenes, polyolefins, acrylics, amorphous polyolefins, ABS, and AS, biodegradable resins such as polylactic acid and polybutylene succinate, and rubber. Among them, aromatic polycarbonate resins and polymethyl methacrylate resins containing 2,2-bis(4-hydroxyphenyl)propane (hereinafter, sometimes abbreviated as bisphenol A) as a monomer component are preferred from the viewpoint of versatility.

[0142] The content of the other resin is preferably 80% by mass or less, more preferably 50% by mass or less, based on the total mass of the resin components of the resin composition of the present invention. Within this range, the balance of other physical properties such as heat resistance and melt processability can be adjusted without significantly impairing the characteristics of the resin composition of the present invention.

[0143] In the resin composition of the present invention, the mass ratio of the polycarbonate resin of the present invention to the cycloolefin resin of the present invention is preferably 99:1 to 15:85, more preferably 95:5 to 35:65, and further preferably 93:7 to 40:60. If it is within the above upper and lower limits, it can be used for molded articles or films.

[0144] (UV absorber) Examples of optical films mounted on displays include surface protection films, polarizer protection films, and retardation films. Films used for these applications need to have ultraviolet ray blocking properties in order to prevent deterioration of liquid crystal molecules and polarizers (PVA) in polarizing plates caused by ultraviolet rays entering from the outside or ultraviolet rays contained in backlight light. From this perspective, the resin composition of the present invention preferably contains an ultraviolet ray absorber.

[0145] In the resin composition of the present invention, when the polycarbonate resin and the cycloolefin resin in the present invention are kneaded, it is preferable to mix an ultraviolet absorber with a tumbler, a super mixer, a floater, a V-type blender, a Nauter mixer, a Banbury mixer, an extruder, etc. The ultraviolet absorbers used in the present invention may be used alone or in combination of two or more kinds.

[0146] The ultraviolet absorbent used in the present invention is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, based on 100% by mass of the resin composition. If it is above the lower limit, the transmittance is high in the visible light region around 430 nm, and transparency is easily obtained. Also, it is preferably 3% by mass or less, more preferably 2.5% by mass or less, and even more preferably 2% by mass or less. If it is below the upper limit, heat resistance can be maintained and an increase in foreign matter due to aggregation of the ultraviolet absorbent can be prevented. As long as the content in the final resin composition is within the above range, the ultraviolet absorber may be added to the resin having a carbonate bond constituting the resin composition or to the cycloolefin resin.

[0147] Preferred ultraviolet absorbents include triazines, benzotriazoles, benzophenones, quinolinones, benzoates, cyanoacrylates, and benzoxazoles, with the triazines, benzotriazoles, and benzoxazoles being preferred from the viewpoints of weather resistance and long wavelength absorption.

[0148] ·Triazine-based UV absorbers Examples of triazine-based ultraviolet absorbers include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,6-diphenyl Phenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy- 4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2, 4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, Examples of such compounds include 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxyphenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-N-octyloxyphenyl)-1,3,5-triazine, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(2-(2-ethylhexanoyloxy)ethoxy)phenol, and 2,4,6-tris(4-butoxy-2-hydroxyphenyl)-triazine.

[0149] Among them, a commercially available product is 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine ("ADEKA STAB LA-F70" manufactured by ADEKA Corporation).

[0150] Benzotriazole-based UV absorbers Examples of the benzotriazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-[2'-hydroxy-3',2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 5'-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)- 2-(2'-hydroxy-3',5'-di-tert-amyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-pentylphenyl), 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and the like.

[0151] Among them, a commercially available product is 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] ("ADEKA STAB LA-31" manufactured by ADEKA Corporation).

[0152] Benzoxazoles Fluorescent whitening agents can also be used for the benzoxazole system. Examples include 7-(dimethylamino)-4-methylcoumarin, 2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene (BASF Japan Ltd. "TINOPAL OB CO"), which is a benzoxazole system, and 4,4'-bis(2-benzoxazolyl)stilbene.

[0153] The 5% weight loss temperature of the ultraviolet absorbent used in the present invention is preferably higher than 250°C. Also, it is more preferably higher than 275°C, and even more preferably higher than 300°C. By being equal to or higher than this lower limit, the ultraviolet absorbent can be prevented from decomposing or volatilizing during melt kneading. This not only allows the ultraviolet absorbent to fully exert its capabilities, but also prevents the accumulation of decomposition products in the extrusion vent, which would interfere with continuous operation, or the accumulation of decomposition products in the T-die, rolls, etc., which would impair the appearance of the film.

[0154] The molecular weight of the ultraviolet absorber used in the present invention is preferably 350 or more, more preferably 400 or more, and even more preferably 450 or more, from the viewpoint of heat resistance. If the temperature is above this temperature, volatilization can be prevented when the resin produced by melt polymerization is kneaded in an extruder. This not only allows the ultraviolet absorber to fully exert its capabilities, but also prevents decomposition products from accumulating in the extrusion vent and hindering continuous operation, or prevents volatile materials from accumulating on the T-die, rolls, etc., and impairing the appearance of the film.

[0155] <Method of producing resin composition> The resin composition of the present invention can be produced, for example, by a method of mechanically melt-kneading each of the above-mentioned components constituting the resin composition. As the melt kneader, for example, a single screw extruder, a twin screw extruder, a Brabender, a Banbury mixer, a kneader blender, a roll mill, etc. can be used. In kneading, each component may be kneaded at once, or a multi-stage division kneading method in which an arbitrary component is kneaded and then the remaining components are added and kneaded may be used. Among them, a method in which each component is continuously charged using a twin screw extruder equipped with a vacuum vent and a resin composition is continuously obtained is preferable from the viewpoint of productivity and quality uniformity. The lower limit of the kneading temperature is usually 150°C or more, preferably 180°C or more, and more preferably 200°C or more. The upper limit of the kneading temperature is usually 280°C or less, preferably 260°C or less, more preferably 250°C or less, and particularly preferably 240°C or less. Within this range, productivity (processing speed of kneading) can be increased while suppressing heat deterioration due to heating by the kneader and heat generation due to shear.

[0156] <Characteristics of resin composition> (Glass transition temperature (Tg)) The resin composition of the present invention preferably has two or more glass transition temperatures. This can provide heat resistance. In addition, from the viewpoint of reducing the amount of deformation of a molded product during heat treatment, it is preferable that at least one of the two or more glass transition temperatures is 130°C or higher. Furthermore, by kneading a polycarbonate resin and a cycloolefin resin having glass transition temperatures within the above ranges at the above mass ratio, an excellent resin composition that satisfies all of heat resistance, low moisture absorption, and processability can be provided.

[0157] (average molecular weight) The average molecular weight of the resin composition of the present invention can be expressed by reduced viscosity. This reduced viscosity is preferably 0.20 dL / g or more, more preferably 0.30 dL / g or more. Below the lower limit, the mechanical strength when molded is weak. The upper limit of the reduced viscosity is preferably 0.60 dL / g or less, more preferably 0.50 dL / g or less. Above the upper limit, the fluidity during molding decreases, the cycle characteristics decrease, and the molding cycle becomes longer. The reduced viscosity of the resin composition can be measured by the method described in the following examples. The temperature for measuring the reduced viscosity was 20°C, and the amplitude was adjusted within the range of ±1°C.

[0158] (Refractive index difference) In the resin composition of the present invention, the absolute value of the refractive index difference between the polycarbonate resin and the cycloolefin resin is preferably 0.02 or less, more preferably 0.015 or less, and even more preferably 0.01 or less. When it is equal to or less than the upper limit, the transparency of the resin composition of the present invention can be improved, and it can be used as a coloring material that develops sharp colors by blending a coloring agent into the resin, or can be applied to members that require transparency, such as optical films.

[0159] (processability) In the resin composition of the present invention, in a re-pellet evaluation performed by the method described below, it is preferable that the cutting of all 100 pellets can be controlled to within 3.0±2.0 mm.

[0160] <Molded products> The resin composition of the present invention can be processed into various molded products by molding methods such as injection molding (insert molding, two-color molding, sandwich molding, gas injection molding, etc.), extrusion molding, inflation molding, T-die film molding, lamination molding, blow molding, hollow molding, compression molding, and calendar molding. Among them, injection molding is preferred in terms of productivity and freedom of design of molded products. The shape of the molded product is not particularly limited, and examples thereof include sheets, films, plates, particles, lumps, fibers, rods, porous bodies, and foams. Sheets, films, and plates are preferred, and plate-shaped molded products are particularly preferred because they are compatible with the characteristics of the resin composition of the present invention. The molded film can also be uniaxially or biaxially stretched. Examples of stretching methods include roll method, tenter method, and tubular method. Furthermore, surface treatments such as corona discharge treatment, flame treatment, plasma treatment, and ozone treatment, which are usually used industrially, can also be performed.

[0161] <Protective film> The film made of the resin composition of the present invention can be used as a protective film such as a surface protective film or a polarizer protective film. The in-plane retardation Re(550) of the protective film is 30 nm or less, preferably 20 nm or less, and more preferably 15 nm or less. The smaller the in-plane retardation Re(550), the more preferable it is.

[0162] When used as a protective film, it may be unstretched or stretched, and if it is too thick, thickness unevenness is likely to occur, and if it is too thin, it may cause breakage during transportation or stretching, so it is usually 5 μm or more, preferably 20 μm or more. Also, it is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 120 μm or less. If it is within the above upper and lower limit range, it can be suitably used for optical products such as surface protective films and polarizer protective films, and electric and electronic parts.

[0163] When used as a protective film, the film may be subjected to a hard coat layer, anti-reflection treatment, anti-sticking treatment, or treatment for the purpose of diffusion or anti-glare, and may be subjected to a surface treatment such as corona discharge treatment or ultraviolet irradiation treatment before adhesion.

[0164] <Method of manufacturing unstretched film> As a method for forming an unstretched film using the resin composition of the present invention, a casting method in which the resin composition of the present invention is dissolved in a solvent and cast, and then the solvent is removed, or a melt film-forming method in which the resin is melted without using a solvent to form a film can be adopted.Specific examples of the melt film-forming method include melt extrusion using a T-die, calendar molding, heat pressing, co-extrusion, co-melting, multilayer extrusion, and inflation molding.The film-forming method for an unstretched film is not particularly limited, but since the casting method may cause problems due to residual solvent, the melt film-forming method is preferable, and among them, the melt extrusion method using a T-die is preferable from the viewpoint of ease of subsequent stretching treatment.

[0165] When forming an unstretched film by a melt casting method, the forming temperature is preferably 280° C. or less, more preferably 270° C. or less, and particularly preferably 265° C. or less. If the forming temperature is too high, defects due to the generation of foreign matter or bubbles in the obtained film may increase, or the film may become discolored.

[0166] However, if the molding temperature is too low, the melt viscosity of the resin becomes too high, making it difficult to mold the raw film and possibly making it difficult to produce an unstretched film with a uniform thickness, so the lower limit of the molding temperature is usually at least 200° C., preferably at least 210° C., and more preferably at least 220° C. Here, the molding temperature of the unstretched film means the temperature during molding in the melt film-forming method, and is usually the value measured by measuring the resin temperature at the die outlet from which the molten resin is extruded.

[0167] Furthermore, if foreign matter is present in the film, it will be recognized as a defect such as light leakage when used as a polarizing plate. In order to remove foreign matter in the resin, a method is preferred in which a polymer filter is attached after the extruder, the resin is filtered, and then extruded through a die to form a film. In this case, it is necessary to connect the extruder, polymer filter, and die with piping to transport the molten resin, but it is important to arrange each piece of equipment so that the residence time is minimized in order to minimize thermal deterioration in the piping. In addition, the process of transporting and winding the film after extrusion is performed in a clean room, and the utmost care is required to prevent foreign matter from adhering to the film.

[0168] If the thickness of the unstretched film is too thin, it becomes difficult to handle the film, and wrinkles or breakage may occur during production, so the lower limit of the thickness is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 25 μm or more, and particularly preferably 30 μm or more. Also, the thickness is preferably 450 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, and particularly preferably 160 μm or less.

[0169] Furthermore, if an unstretched film has thickness unevenness, when the film is stretched and used as a retardation film, it will result in retardation unevenness. Therefore, the thickness of the portion to be used as a retardation film is preferably within the set thickness ±3 μm, more preferably within the set thickness ±2 μm, and particularly preferably within the set thickness ±1 μm.

[0170] The length of the unstretched film in the longitudinal direction is preferably 500 m or more, more preferably 1000 m or more, and even more preferably 1500 m or more. From the viewpoint of productivity and quality, it is preferable to perform continuous stretching when producing the retardation film of the present invention, but usually, condition adjustment is required at the start of stretching to match a predetermined retardation, and if the length of the film is too short, the amount of product that can be obtained after condition adjustment is reduced.

[0171] <Optical film> A film made of the resin composition of the present invention can be used as an optical film such as a retardation film, a polarizing film, a brightness enhancing film, or a diffusion film.

[0172] <Method of manufacturing phase difference film> A retardation film can be obtained by stretching and orienting an unstretched film. As the stretching method, a known method such as longitudinal uniaxial stretching, transverse uniaxial stretching using a tenter or the like, or a combination of these, such as simultaneous biaxial stretching and sequential biaxial stretching, can be used. Stretching may be performed in a batch manner, but continuous stretching is preferable in terms of productivity. Furthermore, compared with the batch manner, the continuous manner can obtain a retardation film with less variation in the phase difference in the film plane.

[0173] The stretching temperature is in the range of (Tg-20°C) to (Tg+30°C), preferably (Tg-10°C) to (Tg+20°C, and more preferably (Tg-5°C) to (Tg+15°C), relative to the glass transition temperature (Tg) of the resin composition used as the raw material. When a resin composition has multiple Tg's, the average Tg value is used as the standard for evaluation.

[0174] The stretching ratio is determined depending on the desired retardation value, and is preferably 1.1 to 4 times, more preferably 1.2 to 3.5 times, in each of the longitudinal and transverse directions. If the stretching ratio is too small, the effective range in which the desired orientation degree and orientation angle can be obtained becomes narrow. On the other hand, if the stretching ratio is too large, the film may break or wrinkle during stretching. When used as a protective film, a stretching ratio of 1 is preferable.

[0175] The stretching speed is also appropriately selected depending on the purpose, but can be selected so that the strain rate represented by the following formula is preferably 50% to 2000%, more preferably 100% to 1500%, even more preferably 200% to 1000%, and particularly preferably 250% to 500%.

[0176] If the stretching speed is too high, the film may break during stretching, or the optical properties may vary significantly due to long-term use under high temperature conditions.If the stretching speed is too low, not only will the productivity decrease, but the stretch ratio may need to be too high to obtain the desired retardation. Distortion rate (% / min) = {stretching rate (mm / min) / original film length (mm)} x 100

[0177] After the film is stretched, a heat setting process may be performed in a heating furnace as necessary, or a relaxation process may be performed by controlling the width of a tenter or adjusting the roll peripheral speed. The heat setting temperature is in the range of 60°C to (Tg), preferably 70°C to (Tg-5°C), relative to the glass transition temperature (Tg) of the resin composition used in the unstretched film. If the heat treatment temperature is too high, the molecular orientation obtained by stretching may be disturbed, and the desired retardation may be significantly reduced. In addition, when the resin composition has multiple Tgs, the average Tg value is used as a standard for judgment.

[0178] In addition, when a relaxation step is provided, the stress generated in the stretched film can be removed by shrinking the film to 95% to 99% of the width expanded by stretching. The treatment temperature applied to the film at this time is the same as the heat setting treatment temperature. By carrying out the heat setting treatment and relaxation step as described above, it is possible to suppress the fluctuation of optical properties due to long-term use under high temperature conditions.

[0179] The optical film (retardation film) of the present invention can be produced by appropriately selecting and adjusting the processing conditions in such a stretching step.

[0180] The optical film (retardation film) of the present invention preferably has an in-plane birefringence (Δn) at a wavelength of 550 nm of 0.001 or more, more preferably 0.002 or more, and particularly preferably 0.0025 or more. Since the retardation is proportional to the film thickness (d) and birefringence (Δn), by setting the birefringence within the above-mentioned specific range, it is possible to develop a retardation as designed in a thin film, and a film suitable for a thin device can be easily produced.

[0181] The retardation film exhibits flat wavelength dispersion characteristics in which the retardation value hardly changes depending on the wavelength of the measuring light. The Re(450) / Re(550) of the retardation film is preferably 0.97 to 1.05, and more preferably 0.98 to 1.04.

[0182] The retardation film of the present invention preferably has an in-plane retardation Re(550) of 100 nm to 600 nm at a wavelength of 550 nm. When the in-plane retardation Re(550) value is within this range, the film can be suitably used as a 1 / 4λ plate, a 1 / 2λ plate, etc.

[0183] In addition, in the case of a display using a general polarizing plate, the light passing through the polarizing plate is linearly polarized, so when the display is viewed through polarized sunglasses, it may be blacked out depending on the angle. In order to solve this problem, the surface layer of the optical display may be a retardation film. These retardation films can also be suitably used.

[0184] In order to achieve high birefringence, the degree of orientation of the polymer molecules must be increased by lowering the stretching temperature, increasing the stretch ratio, etc., but since such stretching conditions make the film more susceptible to breakage, it is more advantageous to use a resin with superior toughness.

[0185] The optical film (retardation film) of the present invention preferably has a thickness of 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less, although this depends on the design value of the retardation.

[0186] On the other hand, if the thickness is too thin, the film becomes difficult to handle, and wrinkles or breakage may occur during production. Therefore, the lower limit of the thickness of the optical film (retardation film) of the present invention is preferably 10 μm or more, more preferably 15 μm or more.

[0187] <Foreign matter on film> The occurrence of foreign matter in the film not only impairs the quality of the film, but is also undesirable from the viewpoint of film productivity. As described above, the occurrence of foreign matter in the film can be reduced by including an appropriate amount of a specific ultraviolet absorber in the resin composition, and it is particularly effective to prevent the occurrence of unmelted matter during melt kneading and the occurrence of film-forming roll stains due to bleed-out during film formation. In the resin composition of the present invention, the presence or absence of film foreign matter was judged by the bleed-out evaluation and transparency evaluation (total light transmittance and haze) described later.

[0188] <Characteristics of molded products> A molded article using the resin composition of the present invention preferably has the physical properties described below.

[0189] (Light transmittance) The light transmittance at a wavelength of 380 nm of the molded article using the resin composition of the present invention is preferably 60% or less, more preferably 30% or less. If it is less than the upper limit value, it has good visibility when used in an optical film and can cut ultraviolet rays. The transmittance of the resin composition can be measured by the method described in the following examples.

[0190] (Total light transmittance) The total light transmittance of a molded article using the resin composition of the present invention is preferably 85% or more, more preferably 87% or more, and even more preferably 90% or more. If the total light transmittance is equal to or more than the above lower limit, a coloring material that develops sharp colors by blending a colorant into the resin can be obtained, and the resin can be applied to members that require transparency, such as optical films.

[0191] (Hayes) The haze of a molded article using the resin composition of the present invention is preferably 20% or less, more preferably 15% or less, and even more preferably 10% or less. If the haze is less than the lower limit, a colorant can be blended with the resin to produce a coloring material that develops sharp colors, and the resin can be used as a member that requires transparency, such as an optical film.

[0192] (Photoelastic Coefficient) The molded article using the resin composition of the present invention has a photoelastic coefficient of 15×10 -12 Pa -1 It is preferable that the photoelastic coefficient is 15×10 or less. -12 Pa -1 If the photoelastic coefficient is larger than 12×10, when the film is laminated to a polarizing plate as a retardation film and the polarizing plate is mounted on a display device, the stress generated during lamination causes partial stress to be applied to the retardation film due to the viewing environment or the heat of the backlight, resulting in non-uniform retardation change and a significant deterioration in image quality. -12 Pa -1 More preferably, it is 10×10 -12 Pa -1 It is even more preferable that:

[0193] (saturated water absorption rate) The molded article using the resin composition of the present invention preferably has a saturated water absorption rate of 1.6 wt% or less, more preferably 1.5 wt% or less, and even more preferably 1.4 wt% or less. If it is less than the upper limit, the deformation amount of the molded article in a humid and hot environment can be reduced.

[0194] (Bleed-out resistance) When the polyimide film used in the method for producing a molded article described below is peeled off from the molded article using the resin composition of the present invention, it is preferable that no yellow color is transferred to the polyimide film side. In this case, the molded article has excellent bleed-out resistance. EXAMPLES

[0195] Examples of the resin composition are shown below, but the present invention is not limited to the following examples as long as the gist of the invention is not exceeded. The methods for measuring the various properties are as follows.

[0196] <Preparation of unstretched film> Each resin composition pellet or each resin pellet was dried at a temperature of 100°C under a reduced pressure of 200 Pa or less for 12 hours or more. Next, 3 to 5 g of the dried pellets were used in a small heat press machine (Azwan Corporation, AH-2003C AH-1TC) with a length of 14 cm, a width of 14 cm, a spacer according to the thickness, or no spacer depending on the thickness, polyimide films were laid on the top and bottom of the sample, and the sample was preheated at a temperature of 200 to 250°C for 3 minutes, and pressurized at a pressure of 7 MPa for 5 minutes, then removed together with the spacer, cooled, and the polyimide film was peeled off to prepare an unstretched film. The film thickness was measured using a constant pressure thickness measuring instrument conforming to JISK6250. The unstretched film obtained in this manner is referred to as "pressed" in Table 1.

[0197] <Production of molded products> Using a small injection molding machine C, Mobile-0813 (manufactured by Shinko Selvic Co., Ltd.), molded products with a size of 25 mm square and a thickness of 3.2 mm were produced at a molding temperature of 210 to 240° C. The molded products obtained in this manner are referred to as “injected” in Table 1.

[0198] <Wavelength 380nm transmittance> Using an ultraviolet-visible-near infrared spectrophotometer (JASCO Corporation, V-730), the film thickness measurement part of the unstretched film or molded product was set so that it was in the light path, and the measurement mode was transmittance (%), the response was 0.015 sec, the measurement wavelength was 190 to 1100 nm, and the bandwidth was measured at 1 nm intervals. From the obtained transmittance data at each wavelength, the transmittance (%) at a wavelength of 380 nm was read.

[0199] <Haze / total light transmittance> Haze and total light transmittance were measured for the unstretched film or molded product prepared by the above method using a spectrophotometer COH7700 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136. The lower the haze and the higher the total light transmittance, the more excellent the transparency.

[0200] <Photoelastic coefficient> (Sample preparation) A 4.0 g sample of each resin composition pellet or each resin pellet, which had been vacuum dried at 80°C for 5 hours, was pressed in a heat press using a spacer 8 cm wide, 8 cm long, and 0.5 mm thick at a heat press temperature of 200-250°C, preheated for 1-3 minutes, and pressurized at 20 MPa for 1 minute, then removed together with the spacer, and cooled under pressure at 20 MPa for 3 minutes in a water-tube-cooled press to produce a sheet. A sample 5 mm wide and 20 mm long was cut out from this sheet.

[0201] (measurement) The measurements were performed using a combination of a birefringence measuring device consisting of a He-Ne laser, a polarizer, a compensation plate, an analyzer, and a photodetector, and a vibration type viscoelasticity measuring device (Rheology Co., Ltd.'s "DVE-3"). (For details, see the Journal of the Rheological Society of Japan, Vol. 19, p. 93-97 (1991).)

[0202] The cut sample was fixed to a viscoelasticity measuring device, and the storage modulus E' was measured at a frequency of 96 Hz at room temperature of 25°C. At the same time, the emitted laser light was passed through a polarizer, a sample, a compensation plate, and an analyzer in that order, and picked up by a photodetector (photodiode). The amplitude and phase difference with respect to strain were obtained for the waveform of angular frequency ω or 2ω through a lock-in amplifier, and the strain optical coefficient 0' was calculated. At this time, the directions of the polarizer and the analyzer were adjusted to be perpendicular to each other and to form an angle of π / 4 with respect to the stretching direction of the sample. The photoelastic coefficient was calculated from the storage modulus E' and the strain optical coefficient 0' using the following formula. Photoelastic coefficient = 0' / E

[0203] <Repellet> Each resin composition pellet or each resin pellet was passed through an extruder to obtain a strand, and then the case where all 100 pellets excluding fine powder could be controlled to be cut to within 3.0±2.0 mm in the length direction of the strand was marked as "O", and the case where the cutting could not be controlled to 3.0±2.0 mm was marked as "X".

[0204] <Bleed out> In the preparation of the unstretched film described above, when the polyimide film was peeled off and no yellow transfer was observed on the polyimide film side, the film was marked as "O". When transfer was observed, it was determined that the ultraviolet absorber had bled out and the film was marked as "X".

[0205] <Reduced viscosity> Using methylene chloride as a solvent, each resin composition solution or resin solution was prepared at a concentration of 0.6 g / dL. Measurements were performed at a temperature of 20.0°C ± 0.1°C using an Ubbelohde viscometer manufactured by Moritomo Rika Kogyo Co., Ltd., and the relative viscosity ηrel was calculated from the solvent passing time t0 and the solution passing time t according to the following formula. ηrel=t / t0 Next, the specific viscosity ηsp was calculated from the obtained relative viscosity ηrel according to the following formula. ηsp=(η-η0) / η0=ηrel-1 The specific viscosity was then divided by the concentration c (g / dL) to obtain the reduced viscosity ηsp / c. The higher this value, the higher the molecular weight.

[0206] <Water absorption measurement> A square test piece measuring 10 cm in length and 10 cm in width was cut out from the unstretched film and molded product prepared by the above-mentioned method. The test piece was dried for 24 hours or more at a temperature of the lowest glass transition temperature of the resin composition constituting the test piece minus 10°C (Tg-10°C) under a reduced pressure of 200 Pa or less. The mass of the test piece after drying was measured to the order of 0.1 mg, and this value was taken as the dry weight. Next, the dried sample was immersed in desalted water adjusted to 23°C for 72 hours or more. After the immersion, the test piece was taken out of the desalted water, and all the moisture on the surface was wiped off with a clean and dry cloth or filter paper, and then the weight of the test piece was measured to the order of 0.1 mg, and this value was taken as the water absorption weight. The water absorption weight was measured within 30 seconds after taking it out of the water. The saturated water absorption rate (wt%) was calculated from the water absorption weight and the dry weight according to the following formula (iv). Here, the calculated water absorption rate is the saturated water absorption rate. (Water absorption weight - dry weight) / dry weight x 100 = saturated water absorption rate

[0207] <Refractive index> An unstretched film was formed from each resin pellet using a heat press. Approximately 5 g of each resin pellet was placed inside a SUS spacer with a length of 14 cm, a width of 14 cm, and a thickness of 0.1 mm, and polyimide films were laid on the top and bottom of the sample. The sample was preheated at a temperature of 200 to 240°C for 3 minutes, then pressed at a pressure of 7 MPa for 5 minutes, removed together with the spacer, and cooled to produce an unstretched film. A rectangular test piece with a length of 40 mm and a width of 8 mm was cut out from this unstretched film to prepare a measurement sample. The refractive index nD was measured using a multi-wavelength Abbe refractometer DR-M4 / 1550 (manufactured by Atago Co., Ltd.) using a 589 nm (D line) interference filter. The measurement was performed at a temperature of 20°C using monobromonaphthalene as the interface liquid. The refractive index difference is the difference between the refractive index of the polycarbonate resin and the refractive index of the cycloolefin resin in the resin composition of the present invention, and when two or more types of each resin are used in combination, the refractive index of each resin is calculated by multiplying the refractive index value of each resin by the blending ratio. In the resin composition of the present invention, it is preferable that the absolute value of this refractive index difference is a predetermined value or less.

[0208] <Glass transition temperature (Tg)> The glass transition temperature (Tg) was measured using a differential scanning calorimeter NEXTA DSC200 manufactured by Hitachi High-Tech Science Corporation. Approximately 10 mg of each resin composition pellet or each resin pellet was placed in an aluminum pan manufactured by the same company and sealed, and the temperature was raised from 30°C to 200°C at a heating rate of 20°C / min under a nitrogen gas flow of 50 mL / min. After holding the temperature for 3 minutes, it was cooled to 30°C at a rate of 20°C / min. It was held at 30°C for 3 minutes and then heated again to 200°C at a rate of 20°C / min. From the DSC data obtained in the second heating, the extrapolated glass transition onset temperature, which is the temperature at the intersection of a straight line extending the low-temperature side baseline to the high-temperature side and a tangent drawn at the point where the gradient of the curve of the stepwise change part of the glass transition is maximum, was obtained, and this was taken as the glass transition temperature. It should be noted that if at least one of the two or more glass transition temperatures is 130°C or higher, it was evaluated as having excellent heat resistance.

[0209] (Raw materials used]) The abbreviations and manufacturers of the compounds used in the Preparation Examples and Examples are as follows:

[0210] (monomer) ISB: Isosorbide (manufactured by Rocket Fleuret) TCDDM: Tricyclodecane dimethanol (Oxea) SPG: Spiroglycol (manufactured by Mitsubishi Gas Chemical Co., Ltd.) BPFM: Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane BPFM was synthesized by the method described in paragraph number

[0596] of JP2015-25111A. DPC: Diphenyl carbonate (Mitsubishi Chemical)

[0211] (Cycloolefin resin) Resin-5: F3500 (JSR) Resin-6: D4000 (JSR) (Other resins) Resin-7: 7022J (Mitsubishi Chemical)

[0212] (UV absorber) UV absorber-1: LA-F70 (ADEKA)

[0213] (Production Example 1) Resin-1 Polycarbonate resin was polymerized using a continuous polymerization system consisting of three vertical stirred reactors, one horizontal stirred reactor, and a twin-screw extruder. ISB, TCDDM, and DPC were melted in a tank and continuously fed to the first vertical stirred reactor at flow rates of 27.3 kg / hr for ISB, 15.7 kg / hr for TCDDM, and 57.6 kg / hr for DPC. At the same time, an aqueous solution of calcium acetate monohydrate, a polymerization catalyst, was fed to the first vertical stirred reactor in an amount such that 1.5 μmol of calcium acetate monohydrate was added per mol of total dihydroxy compounds. The internal temperature, internal pressure, and residence time of each reactor were as follows: first vertical stirring reactor: 190°C, 25 kPa, 120 minutes, second vertical stirring reactor: 195°C, 10 kPa, 90 minutes, third vertical stirring reactor: 205°C, 4 kPa, 45 minutes, fourth horizontal stirring reactor: 220°C, 0.1 to 1.0 kPa, 120 minutes. The polycarbonate resin extracted from the fourth horizontal stirring reactor was supplied in a molten state to a vented twin-screw extruder TEX30α (manufactured by Japan Steel Works, Ltd.). The extruder has three vacuum vents, where residual low molecular weight components in the resin are removed by volatilization, and phosphonic acid is added as a catalyst deactivator before the first vent at 0.64 ppm by weight relative to the polycarbonate resin, and Irganox 1010, a heat stabilizer, is added before the third vent at 1000 ppm by weight relative to the polycarbonate resin. The polycarbonate resin that passed through the extruder was still in a molten state and passed through a 10 μm Ultipleats candle filter (PALL) to filter out foreign matter. The polycarbonate resin was then extruded in a strand shape from the die, cooled with water, solidified, and cut with a rotary cutter to pelletize. This resin is called "Resin-1". The ratio of structural units derived from each monomer is ISB / TCDDM / DPC=53.9 / 31.1 / 15.0% by mass.

[0214] (Production Example 2) Resin-2 Polymerization was carried out using a batch polymerization apparatus consisting of two vertical stirring reactors equipped with stirring blades and reflux condensers. The polymerization mixture consisted of 37.05 parts by mass (0.254 mol) of ISB, 49.77 parts by mass (0.254 mol) of TCDDM, 108.95 parts by mass (0.509 mol) of DPC, and 8.71 × 10 calcium acetate monohydrate as a catalyst. -4 Part of mass (4.94×10 -6 mol) was charged into the reactor. After the reactor was purged with nitrogen under reduced pressure, the raw materials were dissolved at 150°C for about 10 minutes while stirring. As the first step of the reaction, the internal temperature was reached to 210°C after 40 minutes, and the pressure was reduced while controlling to maintain this temperature. After reaching 210°C, the pressure was reduced to 13.3kPa in 90 minutes. Nitrogen was introduced into the first reactor and the pressure was restored to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature was increased and the pressure was reduced in the second reactor, and the internal temperature was increased to 220°C and the pressure was reduced to 20kPa in 40 minutes. After that, the pressure was further reduced and polymerization was allowed to proceed until the specified stirring power was reached. When the specified power was reached, nitrogen was introduced into the reactor to restore the pressure, and the polycarbonate resin produced was extruded into water and the strands were cut to obtain pellets. This resin is called "resin-2". The ratio of the structural units derived from each monomer was ISB / TCDDM / DPC=36.5 / 49.2 / 14.2% by mass.

[0215] (Production Example 3) Resin-3 The same procedure as in Production Example 2 was carried out, except that the raw materials were changed to 28.91 parts by mass (0.198 mol) of ISB, 58.24 parts by mass (0.294 mol) of TCDDM, and 106.25 parts by mass (0.496 mol) of DPC. This resin is called "Resin-3". The ratio of structural units derived from each monomer is ISB / TCDDM / DPC=28.5 / 57.7 / 13.9% by mass.

[0216] (Production Example 4) Resin-4 ISB 25.34 parts by mass (0.173 mol), SPG 47.76 (0.157 mol), BPFM 27.51 (0.043 mol), DPC 61.20 parts by mass (0.286 mol), and calcium acetate monohydrate 1.05 × 10 -3 Part of mass (5.95×10 -6 mol) was added, and the inside of the reactor was substituted with nitrogen under reduced pressure. The raw materials were dissolved under stirring at 150°C for about 10 minutes under a nitrogen atmosphere. As the first stage of the reaction, the internal temperature was made to reach 220°C after 40 minutes, and the pressure was reduced while controlling to maintain this temperature, and the pressure was reduced to 13.3kPa in 90 minutes after reaching 220°C. Nitrogen was introduced into the first reactor and the pressure was restored to atmospheric pressure, and then the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature was increased and the pressure was reduced in the second reactor, and the internal temperature was increased to 245°C and the pressure was reduced to 20kPa in 40 minutes. After that, the pressure was further reduced and polymerization was allowed to proceed until the specified stirring power was reached. When the specified power was reached, nitrogen was introduced into the reactor to restore the pressure, and the polycarbonate resin produced was extruded into water, and the strands were cut to obtain pellets. This resin is called "Resin-4". The ratio of the structural units derived from each monomer was ISB / SPG / BPFM / DPC=25.0 / 47.4 / 19.5 / 8.0% by mass.

[0217] Example 1 900 parts by weight of pellets of resin-1 obtained in Production Example 1 dried at 80°C for 12 hours were blended with 100 parts by weight of pellets of resin-5, and then extrusion kneading was performed at a cylinder temperature of 240°C and an extrusion rate of 12 kg / hr using a twin-screw extruder TEX30HSS [manufactured by Japan Steel Works, Ltd.] equipped with a vacuum vent, and the resulting resin was extruded into water, and the strand was cut at a speed of 290 r / min using a plastic processing machine SCR-100 manufactured by Isuzu Kakoki Co., Ltd. to obtain pellets of a polycarbonate resin composition. The above-mentioned various evaluations were performed using the obtained polycarbonate resin composition. The results are shown in Table 1.

[0218] (Examples 2 to 10, Comparative Examples 1 to 11) The same operations as in Example 1 were carried out, except that the composition was changed as shown in Table 1. Various properties were evaluated by the methods described above. The results are shown in Table 1.

[0219] [Table 1]

[0220] As is clear from Table 1, the polycarbonate resin compositions of Examples 1 to 10, which contain a polycarbonate resin having a heterocyclic skeleton and / or an alicyclic skeleton and a cycloolefin resin, are excellent in transparency, heat resistance, low moisture absorption, and processability. Furthermore, it is found that Example 7 does not have a bleed-out problem despite containing an ultraviolet absorber.

Claims

1. A resin composition containing two or more resins each containing a heterocyclic skeleton and / or an alicyclic skeleton as a repeating unit, At least one of the resins is a resin having a carbonate bond; At least one of the resins is a cycloolefin resin, A resin composition, in which the content of the cycloolefin resin relative to the total mass of the resin components is less than 86 mass%.

2. The resin composition according to claim 1, wherein the resin having a carbonate bond is a polycarbonate resin containing a structural unit (a) derived from a dihydroxy compound having a moiety represented by the following formula (1): 【Chemistry 1】

3. The resin composition according to claim 2, wherein a mass ratio of the polycarbonate resin to the cycloolefin resin is 99:1 to 15:

85.

4. The resin composition according to claim 2, wherein the structural unit (a) is a structural unit represented by the following formula (2) and / or the following formula (3): 【Chemistry 2】 【Chemistry 3】

5. The resin composition according to claim 2 , wherein the polycarbonate resin contains a structural unit (b) derived from an alicyclic dihydroxy compound.

6. The resin composition according to claim 5 , wherein the structural unit (b) is a structural unit represented by the following formula (4): 【Chemistry 4】

7. The resin composition according to claim 1, comprising an ultraviolet absorber in an amount of 0.01 to 3.0 mass % based on the total mass of the resin composition.

8. The resin composition according to claim 1 , which has two or more glass transition temperatures.

9. 2. The resin composition according to claim 1, having at least one glass transition temperature of 130° C. or higher and a saturated water absorption of 1.6 wt % or lower.

10. 3. The resin composition according to claim 2, wherein an absolute value of a refractive index difference between the polycarbonate resin and the cycloolefin resin at 589 nm is 0.02 or less.

11. The resin composition according to claim 1, having a reduced viscosity at 20°C of 0.20 dL / g or more and 0.60 dL / g or less.

12. A molded article obtained by molding the resin composition according to any one of claims 1 to 11.

13. A film comprising the molded article according to claim 12.

14. An optical film comprising the film according to claim 13.

15. A protective film comprising the film according to claim 13.

16. 13. The molded article according to claim 12, having a haze of 20% or less.

17. The molded article according to claim 12, which has a total light transmittance of 85% or more.

18. 13. The molded article according to claim 12, which has a light transmittance of 60% or less at a wavelength of 380 nm.

Citation Information

Patent Citations

  • Polycarbonate copolymer and method for producing the same

    JP2008024919A

  • Cycloolefin resin film and polarizing plate, optical compensation film, antireflection film and liquid crystal display using the same

    JP2008274136A

  • Copolymerized carbonate resin and method of producing the same

    JP2009215435A

  • Optical film and method for producing optical film

    JP2017040727A

  • Polycarbonate resin film

    WO2016171194A1